2020
DOI: 10.1136/bmjopen-2020-038354
|View full text |Cite
|
Sign up to set email alerts
|

The VRIMM study: Virtual Reality for IMMunisation pain in young children—protocol for a randomised controlled trial

Abstract: IntroductionPain caused by routine immunisations is distressing to children, their parents and those administering injections. If poorly managed, it can lead to anxiety about future medical procedures, needle phobia and avoidance of future vaccinations and other medical treatment. Several strategies, such as distraction, are used to manage the distress associated with routine immunisations. Virtual reality (VR), a technology which transports users into an immersive ‘virtual world’, has been used to manage pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…However the effect of VR in pediatric procedures were mainly observed in dental procedures and other inpatient needle-related procedures such as venipuncture, IV cannulation and port access (15,18,19). The evidence for VR usage in immunization, is limited (21)(22)(23).This present study has shown the feasibility of using VR in childhood immunization, with potential effectiveness in alleviating the pain and anxiety in immunization among children. A future RCT with customized VR design incorporating multiple stakeholders perspective is required to examine the effectiveness of VR in reducing pain and anxiety during immunization among children (24).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However the effect of VR in pediatric procedures were mainly observed in dental procedures and other inpatient needle-related procedures such as venipuncture, IV cannulation and port access (15,18,19). The evidence for VR usage in immunization, is limited (21)(22)(23).This present study has shown the feasibility of using VR in childhood immunization, with potential effectiveness in alleviating the pain and anxiety in immunization among children. A future RCT with customized VR design incorporating multiple stakeholders perspective is required to examine the effectiveness of VR in reducing pain and anxiety during immunization among children (24).…”
Section: Discussionmentioning
confidence: 63%
“…A recent systematic review and meta-analysis concluded that VR mitigates procedural pain and anxiety in pediatrics, but it also reported high risk of bias across studies and significant publication bias (18). Currently, robust evidence on the effectiveness of VR to alleviate pain and anxiety during childhood immunization is limited (21)(22)(23). While Rudnick Chad et al, had shown pain and fear alleviation in children wearing a VR headset, it was a feasibility study with a single arm (21).…”
Section: Introductionmentioning
confidence: 99%
“…Among other possible explanations, perhaps this lack of research can be explained by health care staff overload or low levels of motivation among professionals or toward the support of research [63][64][65][66][67]. However, 2 study protocols have recently been published that will aim to evaluate the effectiveness of VR against pain during vaccination in the pediatric population through RCTs with estimated sample sizes of 100 [68] to more than 400 participants [69].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have proven the feasibility of VR for converting unpleasant emotional experiences into less distressing, potentially pain-free events among children 5 who are exposed to needle procedures such as peripheral intravenous (IV), 13 lumbar punctures or blood draws, 14–17 and vaccinations. 8 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…5,8,[10][11][12][13][14][15][16][22][23][24][25][26][27][28] Further studies have proven the feasibility of VR for converting unpleasant emotional experiences into less distressing, potentially pain-free events among children 5 who are exposed to needle procedures such as peripheral intravenous (IV), 13 lumbar punctures or blood draws, [14][15][16][17] and vaccinations. 8,18 In Saudi Arabia, the Ministry of Health (MOH) has launched a Virtual Reality (VR) intervention program in selected Primary Care Centers (PHCs) around the country, as an initiative to decrease needle phobia and improve children's experience in routine vaccinations. 7 It has been reported that up to 10% of the population avoid vaccination due to needle phobia.…”
Section: Introductionmentioning
confidence: 99%